Muscular dystrophy - Emery, Alan E. H. (Oxford University Press Inc., 2008)
Written specifically for people with muscular dystrophy and their families, this book answers many of the questions asked about how and why muscular dystrophy occurs, and how it will affect the life of a recently diagnosed child